2014
DOI: 10.2174/1567205011666141001120903
|View full text |Cite
|
Sign up to set email alerts
|

Everyday Cognition Scale Items that Best Discriminate Between and Predict Progression From Clinically Normal to Mild Cognitive Impairment

Abstract: Background Impairment in instrumental activities of daily living (IADL) starts as individuals with amnestic mild cognitive impairment (MCI) transition to Alzheimer’s disease (AD) dementia. However, most IADL scales have not shown IADL alterations in clinically normal (CN) elderly. The objective of this study was to determine which of the IADL-related Everyday Cognition (ECog) scale items are most sensitive for detection of early functional changes. Methods We assessed 290 CN and 495 MCI participants from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 20 publications
(28 reference statements)
5
32
0
Order By: Relevance
“…Such findings suggest that there are subtle changes in everyday functioning present even prior to being able to detect clear cognitive impairment that are harbingers of early disease and subsequent cognitive impairment. This is consistent with other studies showing that there are mild functional limitations present in cognitively normal individuals who later go on to be diagnosed with MCI or dementia 13,14,33 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Such findings suggest that there are subtle changes in everyday functioning present even prior to being able to detect clear cognitive impairment that are harbingers of early disease and subsequent cognitive impairment. This is consistent with other studies showing that there are mild functional limitations present in cognitively normal individuals who later go on to be diagnosed with MCI or dementia 13,14,33 .…”
Section: Discussionsupporting
confidence: 93%
“…Finally, while changes in everyday function have traditionally been thought of as late occurring manifestations of AD, a growing body of literature demonstrates that mild changes in everyday function are commonly observed in MCI 11,12 . More recent studies have shown that very subtle changes in complex everyday functional tasks can also be observed in cognitively normal older adults who later go on to develop MCI 13,14 .…”
mentioning
confidence: 99%
“…Specifically, there is a growing body of work demonstrating that individuals with Mild Cognitive Impairment (MCI), often a prodromal state prior to a diagnosis of dementia, show mild changes in their ability to perform everyday activities (Brown, Devanand, Liu, Caccappolo, & Alzheimer's Disease Neuroimaging Initiative, 2011; Burton, Strauss, Bunce, Hunter, & Hultsch, 2009; Peres et al, 2011; Perneczky et al, 2006; Tabert et al, 2002). There is even some evidence to suggest that there are detectable functional limitations in cognitively normal elders who later go on to develop MCI (Farias, Chou, et al, 2013; Marshall et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Although we observed significant differences between the trajectories of functional decline between individuals with and without AD dementia, the effect sizes of functional decline associated with clinical or pathologic diagnosis of AD may have been underestimated. It has been shown care-givers may assesse the functional performance of MCI or AD patients more accurately [14,45,46]. Alternatively, objective measures collected by performance-based tests or digital devices to track a patient’s ability to perform the daily activities of living, such as the patient’s capability to use computer in daily life and whether the patient is taking medications according to prescribed schedule, may give more accurate and quantitative measures of the patient’s functional performance.…”
Section: Discussionmentioning
confidence: 99%